Proceedings of the 48th International Symposium on Microarchitecture 2015
DOI: 10.1145/2830772.2830833
|View full text |Cite
|
Sign up to set email alerts
|

Architecture-aware automatic computation offload for native applications

Abstract: Although mobile devices have been evolved enough to support complex mobile programs, performance of the mobile devices is lagging behind performance of servers. To bridge the performance gap, computation offloading allows a mobile device to remotely execute heavy tasks at servers. However, due to architectural differences between mobile devices and servers, most existing computation offloading systems rely on virtual machines, so they cannot offload native applications. Some offloading systems can offload nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Lee et al proposed an architecture‐aware native code‐offloading framework for mobile devices. The framework does not rely on code annotation and virtualization for offloading.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al proposed an architecture‐aware native code‐offloading framework for mobile devices. The framework does not rely on code annotation and virtualization for offloading.…”
Section: Related Workmentioning
confidence: 99%
“…The RTT of existing high speed is still high for real-time migration of VM workloads. [22][23][24] Lee et al 25 proposed an architecture-aware native code-offloading framework for mobile devices. The framework does not rely on code annotation and virtualization for offloading.…”
Section: Related Workmentioning
confidence: 99%
“…MobiSys ' power constraints) and limited battery life compared to their desktop and server counterparts. A recent study [29] shows that a mobile device is more than 5 times slower than a desktop computer when used to play the same chess game. Therefore, users have to put up with longer waiting time while playing the same game on mobile devices.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research work [22,29,41,31,38,18,43,20,30,42,27,19,35,26] has shown that work offloading is an effective way to improve performance and to prolong battery life of mobile devices. In a work offloading system, the computation-intensive tasks on a mobile device, i.e., the client, are sent to a more powerful server and executed remotely.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation